Harmonisasi Sains dan Agama: Analisis Pemikiran Amin Abdullah tentang Pendidikan Islam Kontemporer - Suparjo, M. Sidiq Pambudi, Bimba Valid Fathony (Hamka Ilmu Pendidikan Islam, 2025)
Harmonizing Science and Religion is essential, especially in contemporary Islamic education and thought. The rapid development of science in the modern era is often considered contrary to the principles established by religion, creating a divide between the two. The urgency to unite the two has become a topic of discussion among contemporary Islamic thinkers, one of whom is Amin Abdullah. He made a breakthrough with the Integration-Interconnection paradigm, an idea that seeks to harmonize Science and Religion. Contemporary Islamic education, where Science must be developed to its full potential, while the role of religion cannot be separated. It is inappropriate to separate the two. This research is a type of library research. This research concludes that Integration and Interconnection in Islamic Education is an effort to eliminate the dichotomy between General Knowledge/Science and Religious Knowledge. Contemporary Islamic education seeks to integrate fundamental Islamic values with modern developments, focusing on the development of individuals who are intellectually, spiritually, and socially balanced. Education that harmonizes Science and Religion helps to shape individuals who are intellectually intelligent and have good character and morality.